2015
DOI: 10.5152/eurasianjmed.2015.119
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Finding of Papillary Thyroid Carcinoma in the Patients with Primary Hyperparathyroidism

Abstract: Objective: The relationship between primary hyperparathyroidism (pHPT) and papillary thyroid cancer (PTC) still remains unclear. We aimed to investigate the incidence of the co-existence of pHPT and PTC. Materials and Methods:Between 2010 and 2013, all patients with pHPT were retrospectively reviewed and those undergoing concomitant thyroid surgery were recorded. Of these, patients with a pathological result showing papillary or micro-papillary thyroid cancer were included into the study. A chart review of 228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The incidence of carcinomas in the cervicomediastinal goiter compared with benign thyroid cervical-mediastinum disease, is around 12.1% (50,51). The association with parathyroid diseases (52)(53)(54)(55)(56) and lymphocytic thyroiditis (57, 58) is also described.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of carcinomas in the cervicomediastinal goiter compared with benign thyroid cervical-mediastinum disease, is around 12.1% (50,51). The association with parathyroid diseases (52)(53)(54)(55)(56) and lymphocytic thyroiditis (57, 58) is also described.…”
Section: Discussionmentioning
confidence: 98%
“…Concomitant pHPT and thyroid malignancy have been reported in several studies since the first cases were reported by Ogburn and Black [ 7 ] in 1956. In pHPT patients, several studies reported the prevalence of papillary thyroid cancer (PTC) to range from 2% to 15% [ 8 , 9 ]. Data on the association between sHPT and PTC is more limited.…”
Section: Introductionmentioning
confidence: 99%
“…The malignancy rate of thyroid nodules in PHPT appears to be similar [13,16,18,20] or even higher [3,21] than that in general patients (5-15%) [22], and while some authors found this association to be coincidental [23], others consider PHPT patients with thyroid nodules "extra suspicious" for thyroid malignancies [24]. The latter was shown in 4 cases of PHPT with sub-centimetric thyroid nodules, benign on fine needle aspirate, that were found to be micropapillary carcinoma intra-operatively by frozen section, leading to an extensive surgery and radio-active iodine therapy [24].…”
Section: Differentiated Thyroid Cancer Incidence In Phptmentioning
confidence: 83%